2012
DOI: 10.7326/0003-4819-157-6-201209180-00003
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide for the Treatment of Cough in Idiopathic Pulmonary Fibrosis

Abstract: Celgene Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 37 publications
0
143
1
3
Order By: Relevance
“…HORTON et al [15] found that thalidomide improved cough-specific QoL in IPF patients, although no objective cough measurements were assessed. Furthermore, thalidomide is known to have a toxic side-effect profile.…”
mentioning
confidence: 99%
“…HORTON et al [15] found that thalidomide improved cough-specific QoL in IPF patients, although no objective cough measurements were assessed. Furthermore, thalidomide is known to have a toxic side-effect profile.…”
mentioning
confidence: 99%
“…Of the 24 randomized participants, 23 were treated (one left the study because of lack of interest), and 20 completed both treatment periods (three dropped out because of worsening health). The demographic characteristics of participants are shown in Table 1 , and further details about the study population can be found in Horton et al 10 Table 2 shows the baseline values of CQLQ, CQLQ subscales, cough VAS, and SGRQ. The CQLQ values are similar to those reported by French et al 9 in their original evaluation of the CQLQ in patients with acute and chronic cough.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with placebo, the mean CQLQ score was 11.4 points lower in the treatment phase and, thus, exceeded this MID. 10 …”
Section: Randomization and Interventionsmentioning
confidence: 99%
“…Knobloch et al (55) reported that the underlying mechanisms of this effect included downregulation of bone morphogenetic protein signaling, an increase in the activity of Wnt and Akt and enhanced apoptosis resistance. In a clinical trial conducted by Horton et al (56), thalidomide treatment was demonstrated to improve coughing and respiratory symptoms, as well as quality of life, in patients with IPF.…”
Section: Role Of Imids In Fibrosis Disease and Ophthalmopathymentioning
confidence: 99%